Environmental exposure and the role of AhR in the tumor microenvironment of breast cancer - Sweeney, Colleen; Lazennec, Gwendal; Vogel, Christoph F. A. (Frontiers in Pharmacology, 2022)
Activation of the aryl hydrocarbon receptor (AhR) through environmental exposure to chemicals including polycyclic aromatic hydrocarbons (PAHs) and polychlorinated dibenzo-p-dioxins (PCDDs) can lead to severe adverse health effects and increase the risk of breast cancer. This review considers several mechanisms which link the tumor promoting effects of environmental pollutants with the AhR signaling pathway, contributing to the development and progression of breast cancer. We explore AhR’s function in shaping the tumor microenvironment, modifying immune tolerance, and regulating cancer stemness, driving breast cancer chemoresistance and metastasis. The complexity of AhR, with evidence for both oncogenic and tumor suppressor roles is discussed. We propose that AhR functions as a “molecular bridge”, linking disproportionate toxin exposure and policies which underlie environmental injustice with tumor cell behaviors which drive poor patient outcomes.